IMPLEMENTASI METODE RESITASI DALAM MENINGKATKAN KEAKTIFAN WARGA BELAJAR PAKET C DI SANGGAR KEGIATAN BELAJAR (SKB) KARAWANG - Putri, Kania Salsabilla; Dewi, Ratna Sari; Hoerniasih, Nia (IKIP Siliwangi, 2025)
This study aims to examine the implementation of the recitation method in enhancing the engagement of Paket C learners in English language learning at SKB Karawang. This research employed a descriptive qualitative method, with data collected through observation, interviews, and documentation. The findings indicate that the recitation method is effective in increasing learning activeness, as reflected in improved participation, willingness to ask questions, involvement in discussions, and the ability to evaluate learning outcomes. The implementation process includes task assignment, execution, and accountability, which foster learner independence and critical thinking skills. Supporting factors in the implementation include positive psychological conditions and guidance from tutors, while inhibiting factors involve learners' physical conditions and an unsupportive learning environment. Therefore, the recitation method can be considered an effective strategy to enhance the learning activeness of learners at SKB Karawang.